GRATITUDE INTERVENTION THROUGH WRITING FOR CAREGIVERS AT SOCIAL WELFARE INSTITUTIONS - Iyulen Pebry Zuanny; Rifqa Aulia Hafifuddin; Karjuniwati Karjuniwati (Journal of Social and Economics Research, 2025)
Caregivers at social welfare institutions face various psychological challenges in carrying out their caregiving duties, such as stress, emotional exhaustion, difficulties managing children’s behavior, and the demand to consistently provide high-quality care. One approach that can be used to improve emotional regulation is a gratitude intervention through writing. This study aims to explore the implementation of a gratitude intervention through writing and its impact on emotional regulation among caregivers at SOS Children’s Villages in Banda Aceh and Meulaboh. The study employed a mixed-methods approach, involving 25 caregivers selected using total sampling. The intervention was conducted over six hours across five sessions: gratitude psychoeducation, writing about psychological experiences, cognitive restructuring through gratitude, drawing lessons, and writing expressions of gratitude. Data were collected using a gratitude scale and reflective worksheets, which were analyzed using both quantitative and qualitative descriptive methods. The study results show that prior to the intervention, most caregivers experienced negative emotions such as sadness, disappointment, frustration, anxiety, and guilt. After participating in the intervention, participants reported a shift toward more positive emotions, such as increased calmness, sincerity, patience, self-acceptance, and the ability to think positively. These findings suggest that a gratitude intervention through writing has the potential to be an effective strategy for improving emotional regulation and psychological well-being among caregivers in social welfare institutions.